Roadmap on optical metamaterials. (9th August 2016) - Urbas, Augustine M; Jacob, Zubin; Negro, Luca Dal; Engheta, Nader; Boardman, A D; Egan, P; Khanikaev, Alexander B; Menon, Vinod; Ferrera, Marcello; Kinsey, Nathaniel; DeVault, Clayton; Kim, Jongbum; et al.
Abstract: Optical metamaterials have redefined how we understand light in notable ways: from strong response to optical magnetic fields, negative refraction, fast and slow light propagation in zero index and trapping structures, to flat, thin and perfect lenses. Many rules of thumb regarding optics, such as μ = 1, now have an exception, and basic formulas, such as the Fresnel equations, have been expanded. The field of metamaterials has developed strongly over the past two decades. Leveraging structured materials systems to generate tailored response to a stimulus, it has grown to encompass research in optics, electromagnetics, acoustics and, increasingly, novel hybrid material responses. This roadmap is an effort to present emerging fronts in areas of optical metamaterials that could contribute and apply to other research communities. By anchoring each contribution in current work and prospectively discussing future potential and directions, the authors are translating the work of the field in selected areas to a wider community and offering an incentive for outside researchers to engage our community where solid links do not already exist.